Analysis of Cash Holding and Firm Size on Firm Value in Coal Mining Companies Listed on the Indonesia Stock Exchange - Mursalini, Wahyu Indah; Sriyanti, Esi; Septiawati, Laras (Journal of International Accounting, Taxation and Information Systems, 2025)
This study will look at the impact of cash reserves and company size on corporate value (a case study of coal mining sub-sector businesses listed on the IDX between 2017 and 2022). In this study, 17 coal mining companies listed on the Indonesian stock exchange were chosen using a purposive sample method. This research uses quantitative data. The results of the statistical research indicate that cash reserves have a considerable impact on the value of the enterprises under consideration. This is demonstrated by the t-test results: 2.549 > t-table 1.668, significance 0.014 > 0.05. Thus, it can be determined that Cash Holding influences Company Value. The statistical analysis results indicate that Firm Size significantly influences Company Value in the examined companies. This is demonstrated by the t-value of -1.801 < t-table 1.668 and a significance of 0.078 > at a significance threshold of 0.05. As a result, it is reasonable to conclude that the Cash Holding variable has a large influence on Company Value. Cash reserves and firm size have a significant impact on the value of a firm. The f test confirms this, with a significance level of 0.021 < 0.05 and an f-value of 4.182 < f-table 3.134. This is demonstrated by the R Square value of 0.154, or 15.4%, with the remaining 84.6% influenced or clarified by parameters not examined in this study, such as Net Profit Margin, Return On Assets, and Debt To Equity Ratio.